2006
DOI: 10.4209/aaqr.2006.06.0001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Roadside Fine Particulate Carbon and its Eight Fractions in Hong Kong

Abstract: Simultaneous measurements of PM 2.5 mass, OC and EC and eight carbon fractions were conducted in a roadside microenvironment around Hong Kong for a week in May-June 2002 to obtain the characterization of freshly emitted traffic aerosols. Traffic volume (diesel-powered, liquefied-petroleum gas and gasoline-powered vehicles), meteorological data, and sourcedominated samples were also measured. PM 2.5 samples were collected on pre-fired quartz filters with a mini-volume sampler and a portable fine-particle sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 31 publications
5
31
1
1
Order By: Relevance
“…Therefore, this OC fraction may be associated with vehicle emissions based on the above assumption. This is in agreement with the study of Cao et al (2006) and Liu et al (2006), who found enhanced OC3 in vehicle emissions.…”
Section: Characteristics Of Temperature-resolved Carbon Fractions Of supporting
confidence: 82%
“…Therefore, this OC fraction may be associated with vehicle emissions based on the above assumption. This is in agreement with the study of Cao et al (2006) and Liu et al (2006), who found enhanced OC3 in vehicle emissions.…”
Section: Characteristics Of Temperature-resolved Carbon Fractions Of supporting
confidence: 82%
“…The high percentage of VOCs is due to vehicles and industries like refineries. The percentage of OC2 fraction in TC was 24%, 26%, 32% and 27% at C, K, R and I sites, while OC3 in TC was 20-22% and OC4 in TC was between 10-14% (Cao et al, 2006) indicated that high OC2 and OC3 are associated with presence of gasoline and liquefied petroleum gas emissions and secondary organic carbon. The OC4 components may consist of a mixture of high boiling point hydrocarbons e.g PAHs.…”
Section: Eight Carbon Fractions In Pm 25mentioning
confidence: 98%
“…In a study conducted by Cao et al (2005) found that the average indoor and outdoor concentrations of 24 h PM 2.5 were 56.7 and 43.8 µg/m 3 , respectively, at residential homes in Hong Kong. It was found that the concentrations of air particulates of indoors sometimes were much higher than that of outdoors (Lee et al, 2000;Ramachandran et al, 2000;Adgate et al, 2002;Ramachandran et al, 2003;Cao et al, 2006). Therefore, studies on indoor particles characteristics are as important as the outdoors'.…”
Section: Introductionmentioning
confidence: 99%